2019
DOI: 10.1563/aaid-joi-d-18-00158
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Implant Shape on Primary Stability of Implants With a Thread Cutting and Forming Design: An Ex Vivo Study

Abstract: The design of an implant has a great effect on primary stability. The purpose of this study was to determine the differences in primary stability between straight and tapered Neoss ProActive implants in type I and type III bones using resonance frequency analysis (RFA) and electronic percussive testing (EPT) methods. Fresh cow vertebrae and pelvis were used as models of type III and type i bone, respectively. Implants of 2 different designs—straight and tapered Neoss ProActive implants with a thread cutting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface. 3,[7][8][9][10][11] With regard to implant diameter, studies [12][13][14][15] have shown that narrow-(<3.3 mm) and standard-(4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers. However, achievement of PS is often challenging when implants are placed in type-IV bone (soft bone), which usually comprises the posterior maxillae.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tapered dental implants demonstrate a higher mechanical stability compared with cylindrical dental implants 6 . Other variables that may affect PS encompass implant dimensions (length and diameter), surface characteristics (moderately rough or smooth), and number of threads on the implant surface 3,7‐11 . With regard to implant diameter, studies 12‐15 have shown that narrow‐ (<3.3 mm) and standard‐ (4.1 mm) diameter dental implants can remain functionally stable in smokers and medically compromised patient in a manner similar to systemically healthy nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Endosteal implants are anchored into bone tissue. Their long-term success and retention depend firstly on primary implant stability (PIS) and, ultimately, on the biological stability mediated by osseointegration (OI) [4][5][6][7][8][9]. PIS refers to the avoidance of micromovements at the implant-bone interface during early postoperative bone remodeling, which is determined by physical interactions of the implant with surrounding bone tissue [10].…”
Section: Introductionmentioning
confidence: 99%
“…PIS refers to the avoidance of micromovements at the implant-bone interface during early postoperative bone remodeling, which is determined by physical interactions of the implant with surrounding bone tissue [10]. It degrades gradually after the initial implant placement [4][5][6][7][8][9]. Meanwhile, a transition occurs wherein bone remodeling during OI -defined as the development of a mechanical connection between living bone tissue and an implant body -brings the implant surfaces into tight apposition with stabilizing bone tissue [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation